Treatment Supervision and Medication Adherence among Tuberculosis Patients Within A Health Belief Model Framework - Sri Suwarni; Zakky Cholisoh; Laras Utami; Metrikana Novembrina; Livana PH; Dona Yanuar Agus Santoso (Indonesian Journal of Global Health Research, 2025)
Indonesia is the country with the second-highest number of tuberculosis (TB) cases in the world after India. TB is a chronic infectious disease caused by Mycobacterium tuberculosis. TB treatment requires a long duration and must be carried out consistently, which often leads to patients discontinuing their medication before completing the therapy. Patient adherence to medication plays a crucial role in determining treatment success. One of the factors influencing TB patients’ adherence is the role of the Directly Observed Treatment (DOT) supervisor or Pengawas Minum Obat (PMO). This study aims to determine the relationship between the role of PMO in supervising medication intake using the Health Belief Model (HBM) approach and medication adherence among TB patients at RSD K.R.M.T Wongsonegoro, Semarang City. This survey-based study employed a non-experimental correlational quantitative design with prospective data collection. The instrument used was a structured questionnaire. The total sample consisted of 72 participants, selected using a non-probability purposive sampling technique. The instrument was tested for question content by experts and for validity and reliability using the Spearman correlation. Data were analyzed using bivariate analysis with the Spearman Rho test. The results showed an r-value of 0.385, indicating a moderately strong correlation, with a significance value of 0.001 (< 0.05). These findings demonstrate a significant relationship between the role of the TB PMO and medication adherence using the Health Belief Model (HBM) as a framework for understanding and predicting health behaviors based on individuals’ attitudes, beliefs, and perceptions of health risks. The role of the Directly Observed Treatment supervisor (PMO) has a significant relationship with TB patient medication adherence when assessed using the HBM approach.